سيميائية الشخصية في قصص محمد الكامل بن زيد بيوت صغيرة نوافذ كبيرة انموذجا - مريم، رزوق, غمام نواس، حواء; بن تيشة، حياة (My University, 2022)
يتناول هذا البحث جانبا من جوانب البناء السردي في القصة وهو "الشخصية"، حيث تعتبر هذه الأخيرة العمود الفقري الذي تقوم عليه كل القصص، والركيزة الأساسية في بناء النص السردي، حيث تتمحور حولها أحداث العمل الفني بمختلف أجناسه، وتعد القنديل الذي ينير للكاتب ويشق له الطريق لكتابة نصه، وتبيان دور الشخصية داخل العمل السردي من حيث الدور المؤدى من طرفها، ولهذا كانت دراستنا معنونة ﺒ : سيميائية الشخصية في المجموعة القصصية "بيوت صغيرة ..نوافذ كبيرة" لمحمد الكامل بن زيد، حيث حاول أن يبين لنا من خلال مجموعته القصصية، تلك المشاكل التي تواجهه الشخصيات من قبل مجتمعهم وعدم التأقلم معهم، وخصوصا في القصص التي تم اختيارها وهن: "صناديق قديمة والحوت الأزرق وغربة"، "ومأتم وهاكر وشرنقة" كان تسليط الضوء على هذه القصص لأنهم المحور الرئيسي من خلال دراستنا لهذا العمل السردي، حاولنا من خلال هذه المجموعة القصصية كشف وتحليل للشخصيات المتواجدة في السرد القصصي، معتمدين على المنهج السيميائي لأنه منهج تحليلي يتيح للباحث الحرية في التحليل، وتنقسم الدراسة إلى مقدمة، ومدخل للموضوع، وفصلين تطبيقين وهما عبارة عن دراسة تطبيقية سيميائية لشخصيات المجموعة القصصية، وخاتمة توصلنا فيها إلى جملة من النتائج ملخصها: أن اختيار "محمد الكامل بن زيد" لشخصيات قصصه، كان بطريقة بسيطة وسهلة وجعل هذه الطريقة وسيلة يوصل بها فكرته إلى أفراد المجتمع أن يتقبلوا هذه الفئات بسيئاتهم وحسناتهم. Abstract of the study This research dealt with an aspect of the narrative construction in the story, which is the personality. Its edge slept, and it was the lantern that illuminated the writer and paved the way for him to write a text, “And Sheyan Dor.” That is why our study was entitled: Personal Semiotics in the Solar System - Small Houses.. Big Windows” by Muhammad al-Kamil bin Zaid, where he tried to show us through his collection of stories, Those problems that the characters face from their society and the lack of adaptation with them, especially in the stories that were selected, which are the story of “Old Sundiya, the Blue Whale and Ghorba”, “Matam, and Deceptive and Sharia.” These stories were highlighted because they are the main focus through our study of this narrative work, we tried Through this collection of stories, they revealed and analyzed the characters present in the storytelling, relying on the semiotic approach because it is an analytical method that the researcher follows freedom in analysis, and the study is divided into an introduction, an introduction to the topic, and two applied chapters, namely It is an applied semiotic study of the personalities of the divisional group, and a conclusion in which we reached a number of conclusions, summarizing: The selection of Muhammad Al-Kamel bin Zayed for the characters of his stories was in a simple and easy way, and making this method a means of conveying his idea to the members of society to accept these groups their bad and their good.
Keywords: سيميائية – الشخصية - المجذوب – الحالم – المجنون – المغترب – المتمرد – المهمش بيوت صغيرة – نوافذ كبيرة - محمد الكامل بن زيد; semiotics – The personality – Majdoub – Dreamer – The crazy – expatriate – The rebel - Marginalized - Small houses – Big windows – Muhammed al-kamil bain zaid.